Antiproliferative activities of halogenated pyrrolo[3, 2-d]pyrimidines. Issue 15 (1st August 2015) - Temburnikar, Kartik W.; Ross, Christina R.; Wilson, Gerald M.; Balzarini, Jan; Cawrse, Brian M.; Seley-Radtke, Katherine L.
Graphical abstract: Abstract: In vitro evaluation of the halogenated pyrrolo[3, 2- d ]pyrimidines identified antiproliferative activities in compounds 1 and 2 against four different cancer cell lines. Upon screening of a series of pyrrolo[3, 2- d ]pyrimidines, the 2, 4-Cl compound 1 was found to exhibit antiproliferative activity at low micromolar concentrations. Introduction of iodine at C7 resulted in significant enhancement of potency by reducing the IC50 into sub-micromolar levels, thereby suggesting the importance of a halogen at C7. This finding was further supported by an increased antiproliferative effect for 4 as compared to 3 . Cell-cycle and apoptosis studies conducted on the two potent compounds 1 and 2 showed differences in their cytotoxic mechanisms in triple negative breast cancer MDA-MB-231 cells, wherein compound 1 induced cells to accumulate at the G2/M stage with little evidence of apoptotic death. In contrast, compound 2 robustly induced apoptosis with concomitant G2/M cell cycle arrest in this cell model.